Data Science Approach for Social Media Analytics - Kavya.V, N. Harini (International Journal of Advanced Science and Technology, 2020)
Today there is an exponential growth and widespread dependence of users on digital social media. Deep learning has gained increased attention because of its huge processing power and data analytics capability. Many works in the literature has focused on risks associated with sharing sensitive data using Machine learning models to understand human behavior. An attempt has been made in this work to evaluate the performance of Deep learning model to understand human behavior. The experimentation results clearly reveal that Deep learning models provide a better prediction for controlling the dynamics of information spread among peers